"A man's mouth is his castle": The midcentury fluoridation controversy and the visceral public. Issue 1 (2nd January 2016) - Johnson, Jenell
ABSTRACT: This essay forwards a theory of "visceral publics" through a case study of a bitter public health controversy in a small midcentury New England town. Proponents of fluoridation claimed that it yielded significant positive health outcomes, while opponents charged that the measure was politically suspect and physically dangerous. In this essay, I analyze the controversy as it took shape in letters to the editor and argue that the root of opposition to fluoridation was not in political ideology, as scholars have often claimed, but in a perceived threat to the body's boundaries, which created intense feelings. Although visceral publics are most clearly observable in controversies over the boundaries of the human body, the essay concludes by showing how the concept may be applied to controversies over the boundaries of the national body as well.